2008
DOI: 10.1063/1.2973666
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the mass spectrometric study of the laser vaporization of graphite

Abstract: Reliable experimental data on graphite vaporization and especially on carbon vapor composition exist only up to 2500–3000 K. Data measured at higher temperatures are questionable due to several experimental limitations, such as the difficult temperature determination and the not straightforward correlation of measured temperatures and intensities of signals in mass spectra. That is why a new method of high-temperature mass spectrometry with laser vaporization was developed, in order to extend the accessible te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Several previous laser-assisted studies have reported the mass spectrometric detection of fullerene ions from rBC materials (Rohlfing et al 1984;Spencer et al 2008;Maricq 2009), and high laser power densities (>10 8 W/cm 2 ) have been shown to produce fullerene ions as artifacts of the vaporization process (Buseck 2002). In contrast, low laser power densities (10 3 -10 5 W/cm 2 ) have been shown to be less prone to generate species not originally present and yield carbon cluster distributions similar to thermal desorption results, indicating the minimal influence of laser power density on the resulting carbon clusters, including fullerenes (Buseck et al 1992;Wilson et al 1993;Pflieger et al 2008). …”
mentioning
confidence: 64%
See 4 more Smart Citations
“…Several previous laser-assisted studies have reported the mass spectrometric detection of fullerene ions from rBC materials (Rohlfing et al 1984;Spencer et al 2008;Maricq 2009), and high laser power densities (>10 8 W/cm 2 ) have been shown to produce fullerene ions as artifacts of the vaporization process (Buseck 2002). In contrast, low laser power densities (10 3 -10 5 W/cm 2 ) have been shown to be less prone to generate species not originally present and yield carbon cluster distributions similar to thermal desorption results, indicating the minimal influence of laser power density on the resulting carbon clusters, including fullerenes (Buseck et al 1992;Wilson et al 1993;Pflieger et al 2008). …”
mentioning
confidence: 64%
“…Previous work has shown that neutral C 1 -C 5 carbon clusters represent the main vapor components from heated graphitic carbon materials (Pflieger et al 2008) and the most stable geometries of these clusters are linear (von Helden et al 1993). The positive and negative ion mass spectra for Regal black show that the measured carbon ion fraction in the low carbon category (C 1 C -C 5 C or C 2 ¡ -C 10 ¡ ) is more than 99%.…”
Section: Origins Of Carbon Cluster Ions In Sp-amsmentioning
confidence: 91%
See 3 more Smart Citations